A recently discovered Urartian stele dedicated to the god Ua from Avnik/Erzurum in East Turkey - Işık, Kenan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
What we know so far about Ua, one of the important gods of Urartu, was limited to a few attestations of this name in the Urartian inscriptions. A new inscribed stele fragment found in the vicinity of Avnik in the Erzurum region, in the northwest of the former Urartian Kingdom, reveals new suggestions about the god in question. The inscription on the stele fragment belonging to the Urartian king Sarduri II (756 – ca. 730 BC) helps to reconstruct and complete the missing and broken lines of another inscription previously found in Avnik. The new inscription related to the god Ua indicates that the region of Avnik was probably the place of his worship. At this point, it can be suggested that the cult of Ua existed in the Avnik region before the formation of the Urartian Kingdom and was included in the Urartian pantheon later. In all probability, the god Ua had a cult center here. Finally, judging by the itinerary of Sarduri II, we deal here with military expedition conducted towards the regions of the headwaters of the Araxes River, rather than a visit to the temple of the god Ua. In this study, some results will be shared along with transliteration and translation of the new inscription.